2008
DOI: 10.1080/01443610802344308
|View full text |Cite
|
Sign up to set email alerts
|

Twinning rate in a rural mission tertiary hospital in the Niger delta, Nigeria

Abstract: Twin pregnancy is associated with an increased risk of pre-term deliveries, perinatal morbidity, mortality and maternal complications, especially in developing countries. A descriptive study of all women who had twin pregnancies in a rural mission tertiary hospital over a 7-year period was undertaken. There were a total of 3,351 deliveries and 99 cases of twin deliveries during the study period giving an incidence of 29.5/1,000 or one in 33.8 deliveries. Some 60% of the twins were delivered by caesarean sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
6
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
5
6
1
Order By: Relevance
“…A great number of them persevere with labor cases beyond what they can handle for career and economic reasons, and refer only when complications have set in. Although the perinatal mortality rate of 158.5/1000 births in this study is similar to that reported by other studies,15,19 it is higher than the perinatal mortality rate of 79.6/1000 for singleton births during the study period. Not all the women delivered at the hospital were from Bayelsa State, and some were referred from neighboring states.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…A great number of them persevere with labor cases beyond what they can handle for career and economic reasons, and refer only when complications have set in. Although the perinatal mortality rate of 158.5/1000 births in this study is similar to that reported by other studies,15,19 it is higher than the perinatal mortality rate of 79.6/1000 for singleton births during the study period. Not all the women delivered at the hospital were from Bayelsa State, and some were referred from neighboring states.…”
Section: Discussionsupporting
confidence: 84%
“…This is higher than the 10.6%15 but lower than the 60%19 reported from previous studies. The reason is that most of these patients were referred from private and public primary and secondary health facilities within and sometimes outside Bayelsa.…”
Section: Discussioncontrasting
confidence: 70%
“…Perhaps more so, as the complete prevention of adverse prenatal factors remains an unattainable goal worldwide and the costs associated with even apparently healthy full-term multiple births may be prohibitive in resource-poor settings (35). The significant association of multiple gestations with the female sex in this study also warrants further research considering the dearth of corroborating evidence in the literature from this region (26), although some comparable studies also found a higher proportion of female twins in their population (9,12). While no direct association was found between multiple gestations and hearing screening failure, the risk of sensorineural hearing loss secondary to ineffective or inappropriate management of the other perinatal outcomes, such as severe hyperbilirubinaemia which is not uncommon in many resource-poor settings, should not be overlooked.…”
Section: Discussionsupporting
confidence: 52%
“…While multiple births are often disproportionately represented among preterm, low birthweight or intrauterine growth-restricted infants, maternal and infant morbidities following multiple pregnancies, unlike perinatal mortality rates, have not been thoroughly described in developing countries (9-13). Additionally, since preterm births, low birthweight, and intrauterine growth restriction are prominent risk factors for adverse neurodevelopmental outcomes worldwide, a better characterization of the perinatal consequences of multiple pregnancies should be helpful in facilitating resource allocation and closer developmental surveillance for infants at risk of developmental delays (6,14-18).…”
Section: Introductionmentioning
confidence: 99%
“…However, until now relatively few twin studies have been carried out in Sub-Saharan Africa [1,2,4,10]. Of the studies done [2,6,8-16], most have examined hospital records retrospectively [1,2]. Therefore there is a need of prospective cohort studies focusing specifically on the epidemiological and clinical aspects of twinning.…”
Section: Introductionmentioning
confidence: 99%